Cooperative household models - Patricia Apps; Ray Rees (Institute for the Study of Labor (IZA), 2007)
We set out a general framework for cooperative household models, based on Samuelson's idea of a household welfare function, but extending it to incorporate the key insight from Nash bargaining models - the idea that the household's preference ordering over the utility profiles of its members depends on their wage rates (or prices more generally) and non-wage incomes. Applying reasonable general restrictions on the effects of changes in these variables allows derivation of the general implications of cooperative models.
Keywords: 330; Generalisation; household; model; Haushaltsökonomik; Soziale Wohlfahrtsfunktion; Verhandlungstheorie; Theorie